Determination of polycyclic aromatic hydrocarbons in beverage by low density solvent based-dispersive liquid-liquid microextraction-high performance liquid chromatography-fluorescence detection - Loh, Saw Hong; Chong, Yu Ting; Khairun Nisa Nor Afindi,; Norshima Abdullah Kamaruddin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
A simple and fast dispersive liquid-liquid microextraction (DLLME) technique using organic solvent lighter than water has been developed for the extraction of selected polycyclic aromatic hydrocarbons in green tea, chrysanthemum tea and coffee beverage. The 1-octanol and acetonitrile were pre-mixed and injected into the sample solution. After dispersing, the cloudy solution was subjected to centrifugation to separate the solution into 2 phases, where the micro-droplet of 1-octanol was clearly floated on the top layer. The 1-octanol extract was then diluted and injected into high performance liquid chromatography-fluorescence for the quantitative analysis. The technique offered rapid analysis as the 1-octanol was homogeneously dispersed in the sample solution thus speeding the analytes diffusion. Under the optimized extraction conditions, the technique achieved trace detection limits in the range of 0.001 to 0.3 μgL-1 for the targeted analytes, namely phenanthrene, fluoranthene and benzo[a]pyrene. The method was successfully applied to the spiked green tea, chrysanthemum tea and coffee beverage samples with good average relative recoveries obtained in the range of 86.7 to 103.0%. The utilization of low density organic solvent as extraction solvent has allowed for easier operation and eliminated the use of hazardous halogenated solvent that is commonly applied in DLLME.